2021
DOI: 10.1002/essoar.10504265.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of C, N and Si isotopes as tracers of past ocean nutrient and carbon cycling

Abstract: Review of oceanic distribution, controlling processes, and sedimentary archives of C, N, and Si isotopes • Late Quaternary C, N, and Si sedimentary isotope records demonstrate coupling between the biological pump and atmospheric pCO2 • Cenozoic C, N, and Si sedimentary isotope records indicate large-scale changes in nutrient sources, concentrations, and the carbon cycle ESSOAr |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 193 publications
0
6
0
Order By: Relevance
“…If considering only the euphotic zone, NEP is equivalent to export production, which is an important component of the biological carbon pump (Boyd et al., 2019); indeed, changes in export production have been implicated as a major driver of variations in glacial–interglacial p CO 2 and hence climate (e.g., Berger et al., 1989; Boyle, 1988b; Broecker, 1982; Paytan, 2009). Many of these changes in past export production were inferred on the basis of variations in the cycling of major nutrients and their isotopes (e.g., N, Si; Farmer et al., 2021). The net consumption of nutrients can be interpreted in terms of export production by assuming a fixed proportionality between the major nutrients and C. This proportionality provides the connection linking major nutrient cycles to the sequestration of atmospheric CO 2 via biological productivity.…”
Section: Key Conceptsmentioning
confidence: 99%
See 4 more Smart Citations
“…If considering only the euphotic zone, NEP is equivalent to export production, which is an important component of the biological carbon pump (Boyd et al., 2019); indeed, changes in export production have been implicated as a major driver of variations in glacial–interglacial p CO 2 and hence climate (e.g., Berger et al., 1989; Boyle, 1988b; Broecker, 1982; Paytan, 2009). Many of these changes in past export production were inferred on the basis of variations in the cycling of major nutrients and their isotopes (e.g., N, Si; Farmer et al., 2021). The net consumption of nutrients can be interpreted in terms of export production by assuming a fixed proportionality between the major nutrients and C. This proportionality provides the connection linking major nutrient cycles to the sequestration of atmospheric CO 2 via biological productivity.…”
Section: Key Conceptsmentioning
confidence: 99%
“…Indeed, culture studies consistently showed that phytoplankton assimilated isotopically light Zn from their environment (e.g., John et al., 2007; Köbberich & Vance, 2017; Samanta et al., 2018). It was therefore thought that dissolved profiles of δ 66 Zn would exhibit profiles similar to those of the macronutrients (e.g., δ 13 C, δ 15 N, δ 30 Si; Farmer et al., 2021) and certain micronutrient metals (e.g., δ 114 Cd, δ 138 Ba; Sections 6 and 8, respectively), whereby Zn‐depleted surface waters exhibit isotopically heavy compositions relative to deeper waters. In contrast, the first Zn isotope profile for seawater, obtained by Bermin et al.…”
Section: Zincmentioning
confidence: 99%
See 3 more Smart Citations